Hubungan Pola Makan terhadap Aktivitas Fisik Pasien Gout Atritis Lansia di Wilayah Kerja Puskesmas Moramo - Israwati, Israwati; Tahirudin, Tahirudin; Ananda, Siti Hadrayanti (Jurnal Gizi Ilmiah, 2023)
Gout, a condition characterized by increased levels of uric acid, is one of the health problems experienced by the elderly. Gout, also known as gouty arthritis, is a condition in which the body's purine metabolism is disturbed, resulting in the formation of uric acid. crystals in the joint tissue and increased blood uric acid levels (hyperuricemia). There are several things that can affect uric acid levels in the body, such as diet, physical activity, and lifestyle. In the working area of ​​the Moramo Health Center, the aim of this study was to find out how diet and physical activity affect the prevalence of gouty arthritis in the elderly. 57 people participated in this study, which was conducted in July and August 2022 at the Moramo Health Center. as a sampling method. Questionnaires are used as research instruments for data collection methods. The results showed that 38 people (66.7%) ate well and 19 people (33.4%) ate badly, and 33 people (57.9%). d id exercised little and 24 people did a lot of exercise (42.1%). Chi square analysis and statistical tests showed a p value of 0.00.1, indicating a relationship between diet and physical activity and the prevalence of gouty arthritis among the elderly in the work area of ​​the Moramo Health Center. As a result, to reduce the risk of developing gouty arthritis, the elderly need to reduce purine-rich foods and physical activity